Tingkat Kekebalan Anjing Terhadap Rabies di Kota Ambon = Herd Immunity Against Rabies Among Dogs in Ambon - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The objectives of this study were to reveals factors associated with level of herd immunity against rabies. Four hundred and eighteen blood samples were collected from five subdistricts and 14 villages using stratified and household cluster methods. The result in ELISA test is &#8805